EFEKTIVITAS KOMUNIKASI PEMASARAN MELALUI TIKTOK PADA PANTAI INDAH KAPUK 2 JAKARTA - Angwyn, Adela Vania; Kusuma Negara, I Made; Sasrawan Mananda, IGPB. (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
Marketing activities are one of the important things to do in tourism sector. Marketing communication can be done in various ways, one of which is through Tiktok application. One of tourist destination that viral on tiktok lately is Pantai Indah Kapuk 2 and this study aim to acknowledge the Effectiveness of Marketing Communication through Tiktok Application in PIK 2 Jakarta. The operational variables definition of this study used the AIDA model, which consists of attention, interest, desire and action. Data collection techniques were using through observation, literature study, documentation and distributing questionnaires through google form. The sampling technique in this study used a purposive sampling technique by determining the number of respondents using the Lemshow formula as many as 100 respondents. The data analysis technique used is descriptive quantitative by using the Customer Response Index (CRI). In this study, the results of the effectiveness of Pantai Indah Kapuk 2 marketing communications through the Tiktok application obtained an overall AIDA score of 3.26 which included a very effective scale range, and obtained a CRI value of 57%, which means that Pantai Indah Kapuk 2 communication through the Tiktok application effective.